Cavalcade of Interpretations: The Kasztner train Through the Self-narratives of the Fugitives - Heléna Huhák; András Szécsényi (Zagłada Żydów)
The Kasztner train is one of the most well-known episodes of the Hungarian Holocaust. The action played a highly controversial role in the history of the Jewish self-rescue actions that elaborated in recent historiography. Instead of examining the negotiations between the SS and the Hungarian Zionist Rescue Committee, this study explores how the passengers of the Kasztner train narrated their controversial plight in their diaries, memoirs, and interviews. The inquiry seeks to uncover the history of the Kasztner action from a bottom-up perspective focusing on what was the role of news and rumors about the release in the narratives of the survivors. Hungarian Jewish families, i.e. the “Kasztner Jews” aspired to travel to Palestine, landed finally in Switzerland but directly left from Nazi-occupied Hungary to the Bergen-Belsen concentration camp. The majority of them were spending months in a special sector of the camp between June and December 1944. The circumstances in the Hungarian Camp where the inmates were treated as “hostages” by the Nazis were unusual compared to the other – ordinary – camp sectors of Bergen-Belsen or other concentration camps. Due to this special status, the “Kasztner Jews” were not in emergency considering they did not suffer from starvation, aggression, and illnesses that lead to death. However, they were held under Nazi jurisdiction and were imprisoned by the SS, and were not convinced about their long-awaited survival.